PENGARUH KEPEMIMPINAN, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA MELALUI KOMITMEN SEBAGAI VARIABEL INTERVENING PADA PERANGKAT DESA KESAMBIRAMPAK, DESA KAPONGAN, DAN DESA JUGLANGAN DI KECAMATAN KAPONGAN - Saiful Rijal; Ediyanto Ediyanto; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
Human Resource Management (HRM) encompasses the key functions of managing personnel and human capital within an organization. This includes job analysis, recruitment and selection of candidates, orientation, training, compensation, appraisal, and human resource development. The purpose of this study is to analyze and examine the influence of leadership, compensation, and motivation on performance through commitment as an intervening variable among village officials in Kesambirampak, Kapongan, and Juglangan Villages, Kapongan District. The study population comprises all village officials from these three villages, with the sampling technique determined using a saturation sampling method. Data analysis and hypothesis testing were conducted using the Structural Equation Model–Partial Least Squares (PLS-SEM) approach. The results of the direct effect hypothesis testing, using SmartPLS 3.0, indicate that leadership has a positive but insignificant effect on commitment; compensation has a positive but insignificant effect on commitment; motivation has a positive but insignificant effect on commitment; leadership has a positive but insignificant effect on performance; compensation has a significant positive effect on performance; motivation has a positive but insignificant effect on performance; commitment has a significant positive effect on performance; leadership has a positive but insignificant effect on performance through commitment; compensation has a positive but insignificant effect on performance through commitment; and motivation has a significant positive effect on performance through commitment.